Where Inflammation Met Hamartoma: Radicular Cyst Associated With an Odontome in the Maxillary Anterior Region: A Case Report and Literature Review - Rohit Srikanthan; Ojasvi Sanjay Rambole; Suraj Sathyendra; Minati Jagadev; Mohammed Nahyan (European Journal of Dental and Oral Health, 2026)
Radicular cysts are the most common inflammatory odontogenic cysts and usually arise in relation to a non-vital tooth, whereas odontomas arecommon benign mixed odontogenic lesions that are often discovered incidentally and treated with conservative surgical excision. The coexistence of a radicular cyst with an odontoma in the anterior maxilla appears uncommon in the available literature, making clinic-radiographic recognition and complete surgical management important for diagnosis and rehabilitation. A patient presented with pain and swelling in the upper anterior teeth region for 15 days, with no significant medical history. Clinical examination revealed a labial swelling extending from the right central incisor to the left lateral incisor and palatal swelling extending from the right central incisor to the right canine. Deep dentinal caries were present in both maxillary central incisors. Surgical management consisted of enucleation of the radicular cyst with removal of the odontome through a trapezoidal labial flap, with additional palatal flap elevation for complete retrieval of the odontome, followed by extraction of both central incisors and placement of platelet-rich fibrin with a bone graft before closure.This report highlights the diagnostic challenge posed by a mixed inflammatory and odontogenic hard-tissue lesion in the aesthetic zone and underscores the importance of complete enucleation, histopathologic confirmation, and defect reconstruction in managing extensive anterior maxillary lesions.